Exploring Effective Immersive Approaches to Visualizing WiFi - Rowden, Alexander; Krokos, Eric; Whitley, Kirsten; Varshney, Amitabh (Proceedings - International Symposium on Mixed and Augmented Reality, ISMAR, 2023)
WiFi networks are essential to our daily lives, but their signals are not visible to us. Therefore, it is challenging to evaluate the health of a network or make changes to ensure an optimal configuration. Traditional visualization approaches, such as contour lines, are not intuitive and lead to challenges in the analysis and comprehension of networks. In this paper, we introduce two novel visualizations: Wavelines and Stacked Bars. We then compared these visualizations to the state-of-the-art visualization technique of contour lines. We carried out a user study with 32 participants to validate that our novel visualizations can improve user confidence, accuracy, and completion time for the tasks of router localization, ranking of signal strengths, channel interference, and router coverage. We selected these tasks after extensive discussions with domain experts. We believe that our findings will assist network analysts in visually understanding our increasingly rich signal environments.